Comparison between male and female children in the titer of immunoglobulins and the complement system infected with visceral leishmaniasis (Journal of the College of Basic Education, 2022)
This research aims to know the effect of visceral leishmaniassis.Infection on changes immunoglobulins(IgG,IgM,IgA)and complement And compares with each male and female infections with visceral Leishmaniasis at the age of (1-2)year . The result founded rising in the Titters of( IgG,IgM,IgA) globulins in male and female comparing with Control group it was higher in male group than female group .The titers Of C3 and C4 complement was increased in two groups of male and Female,and was higher in rate in male comparing with the control group. And was higher in male group than female group